Anthropometric Modification can be Useful for Gastro-Esophageal Reflux Disease Symptoms; which Parameter should be Targeted Most? In a Tertiary Care Hospital at Karachi (Medical Forum Monthly, 2024)
Objective: To find out the anthropometric modification can be useful for gastro-esophageal reflux disease symptoms; which parameter should be targeted most? in a tertiary care Hospital at Karachi.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Gastroenterology, Liaquat National Hospital & Medical College, Karachi from February 2009 to March 2010Materials and Methods. Relative sitting of patients were included in the study with no co morbid, non-smoker and non-alcoholic patients. Questionnaires were got filled from them. Logistics regression of the anthropometric measures was computed with the 95% confidence interval.Results: Total 2191 participants were included in our study. 1130 patients (51.6%) were male and 1061 (48.4%) were females, with mean age of 33.92+12.36 years. GERD symptoms were present in 760 patients (34.7%). GERD symptoms were common in patients taking spicy meals (37.2%) and in Urdu speakers (52.5%).Conclusion: In conclusion GERD is common in our population and there is significant inverse association of GERD with Waist hip ratio and waist height ratio.